Critical reading in the construction of oral and written textual genres in Portuguese:: decoloniality and intercultural skills in the school education of the Kanela/Memortunré people. - Silva, Solange Maria Pereira da; Rodrigues, Tiago de Aguiar (The ESPecialist, 2024)
This article discusses the product of the professional master’s degree in Linguistics and Teaching at the Federal University of Paraíba. The objective of the proposal is to offer a training course for a decolonial approach to the study of the most useful oral and written textual genres for the Kanela/Memortunré people. It is the result of action research which aims to collaborate with the community participating in this study. To support this study and the training proposal, we used the framework of Antunes (2003), Bakthin (1997), Paulo Freire (2016), Kleiman (2005, 2006), Mignolo (2003, 2014), Nascimento (2012), Rojo ( 2004), schneuwly; Dolz (1999), Walsh (2009, 2010) among others.